On program of extracurricular mini-football training program for university girl students - A.V. Tamozhanskaya; O.M. Shkola (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
The research is aimed at working out of efficient program for first year girl students' health improvement, which is based on mini-football means' application in extra-curricular activities. Purpose: to substantiate the program of one year mini-football trainings for girl students. Material: one year experiment envisaged participation of 18-20 years' age 56 first year girl students (two groups, 28 people each). The girl students of every group endured different physical loads: group 1 - 70% of specific means and 30% of non-specific; group 2 - 65% of specific means and 35% of non specific. Results: we worked one year efficient program for girl students' health improvement, which was based on application of mini-football specific and non specific means' optimal correlation in extracurricular trainings. We found that optimal correlation of specific and non-specific training loads was 70:30 (%). Practically equal level of workability in both groups was ensured by the following: in group 1 - at the account of special endurance; in group 2 - by means of general physical training. Conclusions: we recommend the program of one-year mini-football trainings, which ensures improvement of physical and technical fitness, rising of girl students organism's and health indicators.